Secretory Gene Recruitments in Vampire Bat Salivary Adaptation and Potential Convergences With Sanguivorous Leeches - Phillips, Caleb D.; Baker, Robert J. (Frontiers in Ecology and Evolution, 2015)
Regulatory evolution is thought to be fundamental to adaptive evolution. However, the identification of specific regulatory changes responsible for adaptation are sparse. Bats of the family Phyllostomidae, owing to their unparalleled rate of ecological and morphological evolution, represent an ideal system to identify regulatory evolution of adaptive significance. Among ecological niche leaps observed in this family, the most dramatic is the evolution of obligate sanguivory by vampire bats, which due to their highly derived phenotype, the sporadic phylogenetic occurrence of blood-feeding, and the adaptive potential of salivary glands, has enabled the development of hypotheses about adaptive molecular phenotypes. Using comparative transcriptomics of vampire bat, outgroup insectivorous bats, and sanguivorous leeches we identify genes that have been convergently recruited as secretory products of salivary glands of vampire bats and leeches. Comparisons of vampire bat to lineages maintaining the primitive chiropteran condition of insectivory indicated gene recruitment of alternative splice variants, and 5′ exon evolution, as the mechanisms producing secretory expression in vampire bats, but not in the insectivorous bats Macrotus and Myotis. Biochemical functions of hypothesized recruited genes explain adaptive benefits to sanguivory by modulating host hemostasis and neural signaling. It is difficult to identify how complex phenotypic change and rapid ecological transition, such as that observed in vampire bats, evolved over a short evolutionary timescale. Results indicate that regulatory evolution controlling tissue-specific splicing patterns has been important to successful adaptation of this lineage. Future studies that leverage emerging long sequence-read technologies, increased sample sizes, and expression and sequence comparisons across other sanguivore lineages will further elucidate roles of alternative splicing and gene recruitment in the remarkable evolution of sanguivory.